Pengaruh Faktor Sosial Ekonomi Terhadap Perilaku Masyarakat Dalam Pengelolaan Sampah Perdesaan di Provinsi Sumatera Barat - Ayu Rahmadani Utama; Dewi Zaini Putri (Jurnal Kajian Ekonomi dan Pembangunan, 2020)
This study aims to determine and analyze the influence of age (X1), gender (X2), education (X3), income (X4), employment status (X5), number of household members (X6), and knowledge (X7) towards rural waste management opportunities in West Sumatra Province. This type of research is descriptive and associative research while the type of data is secondary data. The data used is the 2017 SUSENAS data with documentation data collection techniques from the Central Statistics Agency. Analysis of the data used is logistic regression analysis with all respondents totaling 5,996 people. The results showed: (1) Age was not significant to the opportunities for rural solid waste management in West Sumatra Province. (2) Gender is significant for rural waste management opportunities in West Sumatra Province. (3) Significant education towards rural waste management opportunities in West Sumatra Province. (4) Income is not significant to the opportunities for rural waste management in West Sumatra Province. (5) Significant employment status of opportunities for rural solid waste management in West Sumatra Province. (6) The number of household members is not significant to the opportunities for rural waste management in West Sumatra Province. (7) Insignificant knowledge of opportunities for rural solid waste management in West Sumatra Province.